Children of the changing South : accounts of growing up during and after integration - Dickson, Foster; Molina, David (McFarland & Company, Inc., Publishers, 2012)
"In this collection of memoirs, writers, teachers, scholars and historians recall growing up in the South from the late 1950s to the early 1990s, revealing how the region changed over time, as well as how a Southern childhood varied across time, race, gender, socio-economic status, and geography"--Resumé vydavatele